The Effect of Information Technology And Human Resources Utilization on Hospital Performance Mediated By Lean Hospital Implementation (Case Study of Hospital X) - Nugroho, Wisnu Haryo; Djogo, Y Ony; Rulia, Rulia (Dinasti Publisher, 2025)
This study aims to analyze the Influence of Information Technology Utilization and Human Resources on Hospital Performance Mediated by the Implementation of Lean Hospital (Case Study of Hospital X). The population in this study were all employees at Harapan Sehat Bumiayu Hospital. The sampling method used in this study was probability sampling. The determination of the sample in this study used a saturated/census sample. So the sample size used in this study was all employees at Harapan Sehat Bumiayu Hospital. The results showed that Information Technology has an influence on Lean Hospital. Human Resources have an influence on Lean Hospital. Information Technology has an influence on Hospital Performance. Human Resources have an influence on Hospital Performance. Lean Hospital has an influence on Hospital Performance. Lean Hospital cannot mediate the influence of Information Technology on Hospital Performance. Lean Hospital cannot mediate the influence of Human Resources on Hospital Performance.